Manajemen Media Sosial Sekolah Di Madrasah Tsanawiyah Muhammadiyah 2 Karanganyar - Dona Nur Fitriyanti (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
Social media management is really needed in this super-fast and easy era like today, because technology that is increasingly sophisticated requires humans to be able to use this technology in various aspects of their lives, including in the field of education where social media can provide a myriad of benefits for school institutions. This study aims to determine the use and management of social media at MTs Muhammadiyah 2 Karanganyar. This study uses descriptive qualitative methods, data collection using documentation, observation, and interviews. Data analysis used is interactive analysis. The results of this study indicate that the social media used by MTs Muhammadiyah 2 Karanganyar are YouTube, Facebook, and Instagram which are managed by three teachers (educators). Where YouTube contains content about school activities in the form of extracurriculars. Then Facebook contains content about the logo or symbol of the school. Meanwhile, Instagram contains posts about school activity schedules and educational posters. Finally, WhatsApp is used as a forum for discussing lessons and providing important information. The use of social media in this school is used as a source of information, communication, and promotion for creating a positive image of the school and attracting the interest of prospective students in the intense competition in the era of globalization.